Influência do alagamento nas formas e disponibilidade de fósforo em solo de várzea - Silva, Juliana Brito da (2013)
In irrigated rice, the lowland soils can supply the plants with different amounts of phosphorus due to the source material and the phenomenon that occur in different cycles of oxidation and reduction of these soils. An important factor which regulates the soil availability of phosphorus for plants is the ability to absorb phosphorus. With the overall objective of evaluating the effect of flooding on the forms of phosphorus and on the absorption capacity of phosphorus in lowland soils, two studies have been developed. In the first study, from two larger experiments, conducted for five years (2003/04 to 2007/08), in Solodic Planosol, three treatments have been selected: control, recommended dose of P2O5 as SFT + annual increase of replacement dose and dose Recommended P2O5 as FN + annual increase of replacement dose. Soil samples were collected at two depths (0-2,5 cm and 2,5-5,0 cm) in the respective treatments. The irrigated rice by flooding provides the decrease inorganic forms of labile soil P (RTA and bic 0.5 mol L-1), in the 0-2.5 cm layer in both restevas using the SFT. The form of P most affected by flooding was the one protected inside of microaggregates (Pi hid 0,5 mol L-1) on both stubbles and depths. Organic P had greater participation in total P using the SFT and FN, in both stubbles and depths, after flooding, followed by Pinorganic and finally, the P-residual. In the second study, conducted in the greenhouse, it was evaluated the effect of flooding in the maximum adsorption capacity of phosphorus - CMAP in two lowland soils (Planossolo Haplico and Chernossolo Ebanico), with different adsorption capacity of phosphorus-CMAP, low and high collected at a depth of 0-20 cm, conducted in a flooded and nonflooded structured in a 2x2 factorial design. The determination of CMAP was made by adjusting adsorption isotherm in which subsamples were placed in contact of increasing concentrations of P (1, 2, 4, 5, 10, 20, 30, 40, 50, 60, 70, 80, 100 and 125 mg kg-1 of P) for 16 h. After that, the P determined in equilibrium in the solution, and the Langmuir equation to the data set. After drainage the CMAP of the soil increased taking about 184 days to return to its initial condition before the flooding. The CMAP increases in flooded soil immediately after drainage, and this effect endures for at least 96 days after drainage.